Genetic Analysis of Genealogy from Dental Y-STR DNA with Raman Spectra Method: Literature Review (Indian Journal of Forensic Medicine & Toxicology, 2022)
The role of Forensic odontologist in genealogical analysis is important identification. This is useful in knowingwhether someone has the same or different family lineage. Genealogical analysis can use Y-STR DNA from teethwith Amelogenin. This gene is present in hydroxyapatite crystals on the surface of enamel, dentin and tooth roots.Recent methods obtained from several literatures show that this examination can be performed using a Ramanspectra technique which provides a laser wave stream during PCR analysis. The results of the conclusions fromseveral literatures obtained good accuracy.
Keywords: Forensic Odontologist, Genetic Genealogy, Y-STR, DNA, Y Chromosome, Dental Samples